Rapid separation of Arabidopsis male gametophyte developmental stages using a Percoll gradient - Dupl'áková, Nikoleta; Dobrev, Petre I; Reňák, David; Honys, David (Nature protocols, 2016)
Research investigating the dynamics of male gametophyte (MG) development has proven to be challenging for the plant science community. Here we describe our protocol for separating Arabidopsis MG developmental stages, which is based on the centrifugation of pollen through a discontinuous Percoll concentration gradient. This Percoll gradient can be formed using a pipette, and it does not require a gradient maker. The purity of the isolated developing spores is as high as 70%, and in most separations it is well above 80%. Using this protocol, we can separate four different stages of pollen development-uninucleate microspore (UNM), bicellular pollen (BCP), tricellular immature pollen (TCP) and mature pollen grain (MPG). The duration of the separation procedure, excluding the cutting of flower inflorescences, is 6 h. This is reduced to 4 h when using a vacuum cleaning method to remove the MPGs before the Percoll density separation.
Keywords: časové faktory; Arabidopsis; Cell Separation; oxid křemičitý; Time Factors; pyl; separace buněk; Cell Survival; Centrifugation, Density Gradient; viabilita buněk; povidon; Pollen; Povidone; centrifugace - gradient hustoty; Silicon Dioxide